2021
DOI: 10.1007/s42973-021-00085-9
|View full text |Cite
|
Sign up to set email alerts
|

An experimental comparison of rebate and matching in charitable giving: The case of Japan

Abstract: This study uses a Japanese nationwide sample and experimentally compares rebate and matching, both of which are schemes intended to lower the price of monetary donation. Standard economic theory predicts that the two schemes will have the same effect on individuals’ donation behavior when their donation price is equivalent. However, we conduct an incentivized economic experiment through the Internet on 2300 Japanese residents, and find that matching, which lowers the donation price by adding a contribution fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The preference for matches may arise because of differences in the cooperation versus reward frame, or for other reasons. Sasaki et al (2022) explicitly argued that the cooperation versus rewards frame partly explains higher donations under matches, but they only showed that this difference cannot be entirely explained by confusion or truncation. No positive evidence was offered that framing, per se, is responsible for differences across treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preference for matches may arise because of differences in the cooperation versus reward frame, or for other reasons. Sasaki et al (2022) explicitly argued that the cooperation versus rewards frame partly explains higher donations under matches, but they only showed that this difference cannot be entirely explained by confusion or truncation. No positive evidence was offered that framing, per se, is responsible for differences across treatments.…”
Section: Introductionmentioning
confidence: 99%
“…That is, for a given amount of money a subject is endowed with in the lab, the maximum possible net donation is higher for a match than a rebate. Lukas et al (2011) and Sasaki et al (2022) adopted different methodologies to control for truncation effects, and both continued to find higher donations under a match than a rebate. These experiments rule out truncation as the sole driver of differential behaviour under matches and rebates, but like many of the aforementioned studies, they are unable to offer positive explanations for the residual differences.…”
Section: Introductionmentioning
confidence: 99%